Does Participation in Peer Assisted Learning Programs as a Tutor Lead to an Increase in Teaching Skills Domains? A Quasi-Experimental Study - Khan, Ayub Ahmed; Hussain, Kinza; Asif, Anam; Khan, Mustafa (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the effectiveness of a training program for tutors in peer-assisted learning using objective structured teaching evaluation scores.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital Lahore Medical College and Institute of Dentistry, Lahore Pakistan, from Jul 2022 to Oct 2022.Methodology: Peer-assisted learning was introduced for fourth-year MBBS students rotated in the Ear, Nose, and Throat Department. Twenty-two students, demonstrating strong academic performance and a willingness to teach, were chosen as peer-assisted learning tutors. A series of workshops was conducted to equip these tutors with effective peer-assisted teaching and learning strategies. To gauge the influence of the training on the tutors' teaching abilities, data were collected using 12 stationed Objective Structured Teaching Evaluation scores, both pre-and post-workshop series.Results: Of the 22 students, 16(72.73%) were females, while 6(27.27%) were males. Their ages ranged from 21 - 24 years, with a mean age of 22.45±0.73 years. The study revealed a significant improvement in total Objective Structured Teaching Evaluation raw scores for Peer-assisted learning tutors. The Pre-Objective Structured Teaching Evaluation median score was 35(IQR: 9), exhibiting a substantial increase to 61(IQR: 5.75) Post-Objective Structured Teaching Evaluation, with a statistically significant change (p